A study of desert dermatoses in the thar desert region - Manas Chatterjee; Biju Vasudevan (Wolters Kluwer Medknow Publications, 2015)
Introduction: Desert dermatology describes the cutaneous changes and the diseases affecting those living in the desert. Diurnal variation in temperature is high and is characteristic of the deserts. The lack of water affects daily activities and impacts dermatological conditions. Adaptation to the desert is therefore important to survival. This original article focuses on dermatoses occurring in a population in the Thar desert of India, predominantly located in Rajasthan. Materials and Methods: This is a descriptive study involving various dermatoses seen in patients residing in the Thar desert region over a duration of 3 years. Results: Infections were the most common condition seen among this population and among them fungal infections were the most common. The high incidence of these infections would be accounted for by the poor hygienic conditions due to lack of bathing facilities due to scarcity of water and the consequent sweat retention and overgrowth of cutaneous infective organisms. Pigmentary disorders, photodermatoses, leishmaniasis and skin tumors were found to be more prevalent in this region. Desert sweat dermatitis was another specific condition found to have an increased incidence. Conclusion: The environment of the desert provides for a wide variety of dermatoses that can result in these regions with few of these dermatoses found in much higher incidence than in other regions. The concept of desert dermatology needs to be understood in more details to provide better care to those suffering from desert dermatoses and this article is a step forward in this regard.